What my girlfriend doesn't know - Sones, Sonya (New York : Simon Pulse, 2008)
Fourteen-year-old Robin Murphy is so unpopular at high school that his name is slang for "loser," and so when he begins dating the beautiful and popular Sophie her reputation plummets, but he finds acceptance as a student in a drawing class at Harvard.
Sequel to: What my mother doesn't know.
Accelerated Reader AR
Keywords: Popularity -- Juvenile fiction; Self-esteem -- Juvenile fiction; Dating (Social customs) -- Juvenile fiction; High schools -- Juvenile fiction; Schools -- Juvenile fiction; Artists -- Juvenile fiction; Boston (Mass.) -- Juvenile fiction; Novels in verse